KERJASAMA ANTAR ETNIS MADURA, MELAYU DAN JAWA DI DESA SUNGAI ASAM KECAMATAN SUNGAI RAYA - Azizah, Nur; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Universitas Tanjungpura, 2023)
This study aims to analyze the form of cooperation that occurs between Madurese, Malay, and Javanese ethnicities in Sungai Asam Village, Sungai Raya District. The problem in this study is: how is the form of gotong royong and bargaining between Madurese, Malay, and Javanese ethnicities in Sungai Asam Village, Sungai Raya District? The method used in this study is a qualitative approach with a descriptive method. The data collection techniques used are observation techniques, interviews, and documentation studies. Data collection tools are observation guides, interview guides, and documentation. The data analysis techniques used are data reduction, data presentation, drawing conclusions, and verification. The findings of this study demonstrate that cooperation between Madurese, Malay, and Javanese ethnicities in Sungai Asam Village, Sungai Raya District, is consistent with the theories of James D. Thompson and William J. McEwen. This can be seen from the existence of Gotong Royong cooperation activities, namely road repair activities, mosque renovations, cleaning the environment, and helping in weddings and mourning events. Meanwhile, the bargaining cooperation that occurs involves bargaining prices between sellers and buyers of food goods and other goods needed by the local community. In addition, there is cooperation between financiers and vegetable managers, money exchange, and plantation land development services in Sungai Asam Village, Sungai Raya District.